EFEKTIVITAS KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA ORGANISASI PADA PROSES PEMBELAJARAN DI SEKOLAH MENENGAH ATAS (SMA) - Mega Mustika Ali; Netty Afrimayeni; Nurhizrah Gistituati; Rusdinal Rusdinal; Nellitawati Nellitawati (STKIP Pesisir Selatan, 2025)
This study is a literature review that examines the effectiveness of transformational leadership by school principals in improving organisational performance related to the learning process in senior high schools. The objectives of this study are (1) to formulate the concept and dimensions of transformational leadership in the context of secondary schools, (2) to examine empirical evidence regarding the influence of transformational leadership on teacher performance, school climate, and student learning outcomes, and (3) to identify mechanisms (mediators and moderators) that strengthen or weaken these influences. A systematic review of empirical literature and meta-reviews published in the last 10 years shows consistent findings: transformational leadership is positively correlated and often significantly influences teacher motivation and performance, collaborative culture, Organisational Citizenship Behaviour (OCB), and several indicators of learning process effectiveness. these effects are often mediated by teacher job satisfaction, professional learning communities (PLCs), and school climate, and moderated by contextual factors such as resource support and school culture. Practical implications are discussed for the development of headteacher capacity and educational leadership development policies.